2012
DOI: 10.1042/cbi20110422
|View full text |Cite
|
Sign up to set email alerts
|

Adipoparacrinology – vascular periadventitial adipose tissue (tunica adiposa) as an example

Abstract: Human adipose tissue is partitioned into two large depots (subcutaneous and visceral), and many small depots associated with internal organs, e.g. heart, blood vessels, major lymph nodes, pancreas, prostate gland and ovaries. Since the adipose 'Big Bang' led to the discovery of leptin (Zhang, Proenca, Maffei, Barone, Leopold and Friedman, Nature 1994;372:425-32), adipose tissue has been seen not merely as a lipid store, but as a secretory - endocrine and paracrine - organ, particularly in the pathogenesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…We believe that both studying the adipoparacrinology [28] and "mapping" of the fat will provide a step forward in the understanding of prostate diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that both studying the adipoparacrinology [28] and "mapping" of the fat will provide a step forward in the understanding of prostate diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that adipose tissue, particularly visceral fat, express numerous genes related to adipokine production, which have important roles in the development of atherosclerosis in obese patients [7,24]. Epicardial fat located near to the coronary tree could facilitate the paracrine effects of epicardial adipokines, as part of the pathogenesis of CAD [11,25]. …”
Section: Discussionmentioning
confidence: 99%
“…17 The mechanisms underlying these associations have not been elucidated but current hypotheses implicate the release of free fatty acids and triglycerides from epicardial fat as a source of inflammatory cytokines. 1819 Specifically, the vasa vasorum in the peripheral arterial wall arising from smaller circular and parallel branches of the epicardial coronary arteries provides a ready source of cytokines which may stimulate inflammation and recruitment of macrophages and B-lymphocytes. 19,20,21 These inflammatory processes are connected to the development of atherosclerosis and adverse clinical events.…”
mentioning
confidence: 99%
“…1819 Specifically, the vasa vasorum in the peripheral arterial wall arising from smaller circular and parallel branches of the epicardial coronary arteries provides a ready source of cytokines which may stimulate inflammation and recruitment of macrophages and B-lymphocytes. 19,20,21 These inflammatory processes are connected to the development of atherosclerosis and adverse clinical events. 19,22 …”
mentioning
confidence: 99%